On poisson nonlinear transformations - Ganikhodjaev, Nasir; Hamzah, Nur Zatul Akmar (Hindawi Publishing Corporation, 2014)
We construct the family of Poisson nonlinear transformations defined on the countable sample space of nonnegative integers and investigate their trajectory behavior. We have proved that these nonlinear transformations are regular.